2016
DOI: 10.11648/j.ajpc.20160504.11
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry Based Isotopic Abundance Ratio Analysis of Biofield Energy Treated Methyl-2-napthylether (Nerolin)

Abstract: Methyl-2-napthylether (nerolin) is an organic compound and has the applications in pharmaceutical, and perfume industry. The stable isotope ratio analysis is increasing importance in various field of scientific research. The objective of the current study was to evaluate the effect of the biofield energy treatment on the isotopic abundance ratios of P M+1 /P M (2 H/ 1 H or 13 C/ 12 C or 17 O/ 16 O) and P M+2 /P M (18 O/ 16 O) in nerolin using the gas chromatography-mass spectrometry (GC-MS). The compound nerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 39 publications
(59 reference statements)
0
53
0
Order By: Relevance
“…The natural abundance of each isotope can be predicted from the comparison of the height of the isotope peak with respect to the base peak, i.e. relative abundance in the mass spectra [37,38,42,43]. The natural isotopic abundance of the elements are obtained from several literatures [43][44][45] are presented in Table 1.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The natural abundance of each isotope can be predicted from the comparison of the height of the isotope peak with respect to the base peak, i.e. relative abundance in the mass spectra [37,38,42,43]. The natural isotopic abundance of the elements are obtained from several literatures [43][44][45] are presented in Table 1.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
“…Scientific literature reported that the vibrational energy is closely related with the reduced mass (µ) of the compound and the alteration of the vibrational energy can affect the several characteristics like physicochemical, thermal properties of the molecule [37,38,52,53]. Replacement of the isotopic composition of the magnesium gluconate significantly alters the vibrational energy [41,52,53].…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23,24], nutraceuticals [25,26], organic compounds [27][28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate displays the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [19]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [20], altered antimicrobial sensitivity of pathogenic microbes in microbiology [21][22][23], biotechnology [24,25], genetics [26,27], changing the structure of the atom in relation to the various metals, ceramics, polymers and chemicals materials science [28][29][30], altered physical and chemical properties of pharmaceuticals [31,32], nutraceuticals [33,34], organic compounds [35][36][37], and improved overall growth and yield of plants in agricultural science [38,39].…”
Section: Introductionmentioning
confidence: 99%